2020
DOI: 10.3390/molecules25010178
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiles and Cellular Antioxidant Activities in Chestnut (Castanea mollissima BL.) Kernels of Five Different Cultivars

Abstract: In this study, the phytochemical profiles, total and cellular antioxidant activities of five different Chinese chestnut (Castanea mollissima BL.) cultivars were analyzed. Phenolics, flavonoids as well as phytochemical compounds in five cultivars of chestnut kernels were determined. Results showed that the free forms played a dominant role in total phenolics, flavonoids and antioxidant activities of all five cultivars of chestnut kernels. The cultivar ‘Fyou’ showed the highest total and free phenolic contents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…A high and negative correlation was found between total phenolic content and IC 50 DPPH (r = −0.82). These results are in agreement with those reported by Barreira et al [ 41 ], Chang et al [ 36 ] and Xu et al [ 24 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…A high and negative correlation was found between total phenolic content and IC 50 DPPH (r = −0.82). These results are in agreement with those reported by Barreira et al [ 41 ], Chang et al [ 36 ] and Xu et al [ 24 ].…”
Section: Resultssupporting
confidence: 94%
“…Kalogeropoulos et al [ 33 ] observed total phenolic content of 43.0 ± 2.1 mg GAE/100 g of fresh weight in chestnuts from Greece. Abe et al [ 34 ] found total phenolic content in Brazilian chestnuts of 92 mg/100 g. Nazzaro et al [ 35 ] reported for Italian cultivar “Palomina” a mean value of 76.3 mg GAE/100 g. Chang et al [ 36 ] studied five different Chinese chestnuts ( C. mollissima Blume), and they showed that the total phenolic content ranged from 42.8 to 58.6 mg GAE/100 g fresh weight.…”
Section: Resultsmentioning
confidence: 99%
“…and the average was 284 mg GAE kg -1 d.m. In another study, Chang et al (2020) determined the phenolic content of five types of chestnut produced in China between 243,5-586 mg GAE kg -1 dm. in different cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…The same is true of lignans in nut species; coumarins in seeds of nut plant species have not been characterized well. Some simple and pyrone-substituted coumarin compounds, e.g., aesculin, aesculetin, umbelliferone, and coumestrol, are mostly found in whole almond, Japanese chestnut skin, and Chinese chestnut kernel (Bolling, 2017;Čolić et al, 2017;Tuyen et al, 2017;Chang et al, 2020).…”
Section: Lignans and Coumarinsmentioning
confidence: 99%